HSS revisited: multi‐channel processes mediate trophic control across a productivity gradient. (27th August 2015) - Ward, Colette L.; McCann, Kevin S.; Rooney, Neil; Chase, Jonathan
Abstract Classical food web theory holds that energy channels are regulated by top‐down control with increasing productivity, arising from within‐channel processes. However, these hypotheses do not consider the existence of parallel energy channels linked by shared resource pools and which can fuel generalist predators, imposing trophic control arising from multi‐channel processes. Using 23 large marine food webs, we show that food web responses to increasing productivity are consistent with the apparent trophic cascade hypothesis (ATCH) – with rising productivity predators derive an increasing fraction of their diet from increasingly productive bottom‐up controlled detritus channels, thereby subsidising predator biomass, and in turn strengthening top‐down control in parallel grazing channels. These results testify to a fundamental role of detritus channels specifically and multi‐channel processes in general in mediating food web response to productivity and demonstrate that the ATCH provides an alternative explanation for classical predictions of top‐down control.